CALCULATION OF THE ECONOMIC EFFICIENCY OF THE TECHNOLOGY WHEN OBTAINING SAFFLOWER OIL (American Journal of Interdisciplinary Research and Development, 2022)
The article discusses the results of economic indicators in the production of non-traditional vegetable safflower oil from local raw materials of the Republic of Uzbekistan.